Max Stirner - Newman, Saul. author. aut Link
XI, 234 p.
Keywords: Max Stirner was one of the most important and seminal thinkers of the mid-nineteenth century. He exposed the religiosity behind secular humanism and rationalism, and the domination of the individual behind liberal modes of politics. This edited collection explores Stirner's radical and contemporary importance as a political theorist.